Differences in the chemical structure of the lignins from sugarcane bagasse and straw. (October 2015) - del Río, José C.; Lino, Alessandro G.; Colodette, Jorge L.; Lima, Claudio F.; Gutiérrez, Ana; Martínez, Ángel T.; Lu, Fachuang; Ralph, John; Rencoret, Jorge
Abstract: Two major residues are produced by the sugarcane industry, the fibrous fraction following juice extraction (bagasse), and the harvest residue (straw). The structures of the lignins from these residues were studied by pyrolysis coupled to gas chromatography-mass spectrometry (Py-GC/MS), nuclear magnetic resonance (NMR), and derivatization followed by reductive cleavage (DFRC). Whereas the lignin from bagasse has a syringyl-rich p -hydroxyphenyl:guaiacyl:syringyl (H:G:S) molar composition of 2:38:60, the lignin from straw is guaiacyl-rich (H:G:S of 4:68:28). The compositional differences were also reflected in the relative abundances of the different interunit linkages. Bagasse lignin was primarily β– O –4′ alkyl-aryl ether substructures (representing 83% of NMR-measurable linkages), followed by minor amounts of β–5′ (phenylcoumarans, 6%) and other condensed substructures. The lignin from straw has lower levels of β-ethers (75%) but higher relative levels of phenylcoumarans (β–5′, 15%) and dibenzodioxocins (5–5/4– O –β, 3%), consistent with a lignin enriched in G-units. Both lignins are extensively acylated at the γ-hydroxyl of the lignin side-chain (42% and 36% acylation in bagasse and straw), predominantly with p -coumarates (preferentially on S-units) but also with acetates (preferentially on G-units) to a minor extent. Tetrahydrofuran structures diagnostically arising from β–β-coupling (dehydrodimerization) of sinapyl p -coumarate or its cross-coupling with sinapyl alcohol were found in both lignins, indicating that sinapyl p -coumarate acts as a monomer participating in lignification. The flavone tricin was also found in the lignins from sugarcane, as also occurs in other grasses. Graphical abstract: Highlights: The lignins from sugarcane bagasse and straw are very different to each other. Bagasse lignin is S-rich (H:G:S 2:38:60) and straw lignin is G-rich (H:G:S 4:68:28). Bagasse lignin has mainly β– O –4′ -ethers with minor levels of phenylcoumarans. Straw lignin has higher levels of phenylcoumarans and dibenzodioxocins. Both lignins are extensively acylated at the side-chain γ-OH with p -coumarates.